DIFFERENCES OF CEPHALOMETRIC PARAMETERS IN PRACTICALLY HEALTHY MEN WITH DIFFERENT TYPES OF FACES FROM UKRAINE - Shinkaruk-Dikovitska, M.M.; Kotsyura, O.O.; Orlovskiy, V.O. (World of Medicine and Biology, 2016)
Aim of our work – establish differences cephalometric parameters in practically healthy male with different types of face in general and representatives of the central region of Ukraine.Materials and methodsIn previous survey findings (using a screening questionnaire) to more than 3,500 men aged from 19 to 35 years from different regions of Ukraine authors selected 200 of practically healthy men in the third generation residents of different ethnic territorial regions with susceptible, moderately susceptible and satisfactory for environmental living conditions of the population areas of Ukraine, which carried out cephalometric and computer tomography (using dental cone-beam scanner Veraviewepocs-3D, 0,011-0,048 mSv dose) study.Cephalometric research consisted of determining the parameters of cerebral and facial parts of the head using a large compass with the sliding scale in full-scale system of Martin and soft measuring tape. Cephalometric study was conducted with regard to accepted guidelines and anatomical points.Value facial pointer (morphological index of Garson) received by the appropriate formula. With the value of the indicator till 78.9 men attributed to a group with very broad of face; 79,0-83,9 - broad face; 84,0-87,9 - the average face; 88,0-92,9 - narrow face; 93.0 or more - very narrow face.Statistical analysis of the results was performed using the statistical software package licensed "Statistica 6.1" using nonparametric methods. Reliability of difference values between independent quantitative values were determined using the U- criteria of Mann-Whitney.Results. DiscussionsWhen comparing the differences in cephalometric parameters between practically healthy men of common groups or representatives of central regions of Ukraine with different types of face ascertained that in direction very narrow face
Keywords: cephalometry; practically healthy men; the type of face; regional differences